Salvation: Its Forms and Dynamics in the New Testament - Hultgren, Arland J. (Dialog, 2006)
Salvation takes several forms in the New Testament, including earthly-historical saving acts by the earthly Jesus and eschatological salvation by God's saving work in Christ. The dynamics of salvation can be considered from both anthropocentric and theocentric approaches. In the former salvation is by works, faith, or grace, but issues can be raised about each. In the latter salvation is spoken of as the act of God in Christ (a theopractic approach) or by the act of Christ on God's behalf (a Christopractic approach). Issues arise concerning canonical contexts, whether something happened at the cross effective for humanity and the cosmos, and the scope of redemption.